Development of a Mechatronic Platform for Passive Tactile Stimulation Using a Rotating Drum with Embossed Patterns - Januário, Rodrigo Nogueira (2023)
Tese de mestrado, Engenharia Biomédica e Biofísica, 2023, Universidade de Lisboa, Faculdade de Ciências